(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
Physical education consists a primary sector for young children’s development in Greek Early Years curriculum. It is considered among the core objectives of all curriculums since the establishment of the first Early Years setting back in 1896, a fact that proves its eternal societal value. The aim of physical education at Early Years is the enhancement of motor, social, emotional and cognitive development of children through daily developmentally appropriate movement experiences. Therefore, physical education is not limited to training children in physical skills, but perceives movement as an integral part of their overall learning process. These objectives can be accomplished through the innovative way of working in the Early Years Foundation stage, which relies on an interdisciplinary method and project approach based on children’s ideas and interests.